2014
DOI: 10.1108/ejm-04-2012-0219
|View full text |Cite
|
Sign up to set email alerts
|

Situational variables and sustainability in multi-attribute decision-making

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 71 publications
1
40
1
1
Order By: Relevance
“…Providing more eco-friendly products that consumers experience as being eco-friendly on the brand level would help to reinforce the sustainable consumption behavior of consumers on the micro level and promote sustainable development on the macro level. Consumers trust that companies who have CSR activities are doing their best to develop the sustainability of their product design, manufacturing, and production processes to create more eco-friendly products, which the consumers also experience as truly eco-friendly, and it is crucial for companies to realize this is one of the consumer requirements [79,149]. Electronics companies could use the measures to monitor, for example, how their e-waste management activities are reflected in consumers' brand experiences.…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing more eco-friendly products that consumers experience as being eco-friendly on the brand level would help to reinforce the sustainable consumption behavior of consumers on the micro level and promote sustainable development on the macro level. Consumers trust that companies who have CSR activities are doing their best to develop the sustainability of their product design, manufacturing, and production processes to create more eco-friendly products, which the consumers also experience as truly eco-friendly, and it is crucial for companies to realize this is one of the consumer requirements [79,149]. Electronics companies could use the measures to monitor, for example, how their e-waste management activities are reflected in consumers' brand experiences.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The brand experiences that consumers have can be both communal (associated with society and the environment) and individualistic (having personal value) [76,77], and both kinds of experiences are important for creating brand value [78]. In the case of eco-friendliness, consumers are becoming more influential and informed, and this needs to be taken into account in corporations [79].…”
Section: Sustainable Consumption Driven By Consumers' Brand Experiencesmentioning
confidence: 99%
“…First, customers will have greater certainty about the likely success of a purchase experience when they purchase from a firm which they perceive to have stronger future orientation, because they feel that the business takes the long-term, sustainable view and is more likely to exist in the future as a result of it (Erdem and Swait, 1998;Simpson and Radford, 2014). Indeed, a future oriented business can be characterized as a sustainable business that does not view profit as its sole motive (Simpson and Radford, 2014). Instead, it shifts from a focus on immediate or short-term growth (the aim to grow big fast) towards a longer-term view and continuous development (the aim to get better).…”
Section: The Moderating Role Of Future Orientation In the Relationshimentioning
confidence: 99%
“…By implication, future orientation involves persistence and patience and the commitment of dedicated resource 32 investments over a longer time horizon, thereby sustaining the bonded relationships with consumers in the long run (Bell and Eisingerich, 2007). In this regard, consumers may be aware of the salience of future, looking upon such open and lasting businesses as "role models" by mutually considering the subsequent consequences of their consumption on society (Simpson and Radford, 2014;Welsch and Kühling, 2009). In line with Romani and Grappi (2014), people's consumption related intention and behavior could be the direct outcome of their learning experiences from the observation of a business, causing a symbolic coding of future orientation to be reproduced in consumer's memory and then motivating consumers to imitate decisions toward sustainability and responsibility.…”
Section: Contribution To Theory and Practical Implicationsmentioning
confidence: 99%
“…Situational variables and sustainability in multi-attribute decision making established that the environmental dimension of sustainability is the most influential followed by economic and social [10]. A study on crippled bottom line-measuring and managing sustainability concluded that the relative indicators with focus on people utility compared to planet and people harm seem to be relevant for measuring the level of sustainability [11].…”
Section: Introductionmentioning
confidence: 99%